Moral transhumanism. - Persson, I; Savulescu, J (2010)
In its basic sense, the term "human" is a term of biological classification: an individual is human just in case it is a member of the species Homo sapiens. Its opposite is "nonhuman": nonhuman animals being animals that belong to other species than H. sapiens. In another sense of human, its opposite is "inhuman," that is cruel and heartless (cf. "humane" and "inhumane"); being human in this sense is having morally good qualities. This paper argues that biomedical research and therapy should make humans in the biological sense more human in the moral sense, even if they cease to be human in the biological sense. This serves valuable biomedical ends like the promotion of health and well-being, for if humans do not become more moral, civilization is threatened. It is unimportant that humans remain biologically human, since they do not have moral value in virtue of belonging to H. sapiens.